KINETIČKO MODELOVANJE SUPERKRITIČNE EKSTRAKCIJE ULJA SEMENA AMARANTA - Krulj, Jelena (Journal on Processing and Energy in Agriculture, 2021)
Amaranth seeds contain oil with important nutritional properties, in particular because of essential fatty acids presence, high content of minerals, vitamins, lysine and squalene. In this study, the kinetics of the supercritical fluid extraction of oil from three amaranth seed varieties has been investigated. Average oil content in amaranth seed was 58.2 g/kg, ranging from 54.6 to 61.1 g/kg depends on varieties, while squalene content ranged from 3.3 to 3.8 g/kg with an average content of 3.5 g/kg dry seed. Five empirical kinetic equations were successfully applied for kinetic modeling of extraction. As indicated by the appropriate statistical “goodness of fit” tests (such as the sum of squared errors, the coefficient of determination and the average absolute relative deviation), empirical models show good agreement with experimental data. The mathematical modeling of a process is beneficial to predict the process conduct and furthrtmore extend the procedures from laboratory to industrial scales.
Keywords: ulje semena amaranta, superkritična ekstrakcija, kinetičko modelovanje